Frauenräume im Alten Testament am Beispiel der Siedlung (lectio difficilior, 2009)
The main question of this article is, in which spaces or places women live according to Old Testament texts. As a result of a close reading of the whole Old Testament, over one hundred text passages can be found, where women are placed in a space which is mentioned in the text. These passages can be divided into two main groups: on the one hand those referring to settlements and on the other hand those referring to nature (the world outside the settlement). In this article a closer view is given on text passages referring to settlements like e.g. houses, palaces and cities.